THE ROLE OF PRONUNCIATION INTO CLASSROOM ACTIVITIES. (Conference Zone, 2022)
This article examines the importance of pronunciation and integration into classroom activities with a number of practical concepts. When learners acquire new language, they face several problems, because each language is unique and has particular features. Learning how to speak a new language is not just learning words or grammar. The place of pronunciation in the classroom should be in high position as it requires the awareness of pronouncing and linking sounds or sentences along with intonation. Most teachers mainly focus on grammar, as a result leaner know the language very well, but cannot be understood by listeners. Limited pronunciation skills can influence learners’ self-confidence, demarcate social interactions as a result can negatively affect on the ability. Using the right pronunciation is a key fact in proper communication.